Morphometric of ovaries, follicles, and their relationship with oocyte quality in cattle - Neira-Rivera, Eliana; Velásquez-Penagos, José Guillermo; Cardozo-Cerquera, Jaime Antonio; Velásquez-Penagos, José Henry; Gutiérrez-Parrado, Sonia Lucía; Herrera-León, Rocío Fenney (Agronomía Mesoamericana, 2022)
Introduction. Studies on the structural characteristics of the ovary associated with the quality of the cumulus-oocyte complex (COCs) in cattle contribute to the definition of strategies to improve reproductive efficiency. Objective. To determine the weight and size of the ovaries, follicle quality, and COCs in Zebu females, in order to establish differences between the right and left ovary. Materials and methods. Between March and July 2017, 52 ovaries were obtained from twenty-six Zebu cows. The ovaries and follicles were weighed and measured. The follicles were grouped into three categories: a) <3 mm (TFI), b) 3-6 mm (TFII) and c) >6 mm (TFIII). The follicles quality was determined by the irrigation-translucency technique (TIT) and the COCs by the characteristics of the cytoplasm and cumulus cells as good (CI), fair (CII), and poor (CIII), and by cresyl brilliant blue test were categorized as BCB+ and BCB-. Results. Ovarian length, width and weight were 2.7 ± 0.6 cm, 1.8 ± 0.5 cm, and 7.0 ± 3 g, respectively, with differences for length and weight between the right and left ovary (p<0.01). The highest number of follicles were obtained in TFI (p<0.05). The 88.56 % of the follicles evaluated were of good quality. A total of 52 % and 44.2 % of COCs were classified as CI and BCB+, respectively. When follicle size and COC quality were considered, it was shown that in the TFI group 22 % were IC, 34 % CII, and 44 % CIII, and in the TFII group 31 % were IC, 21 % CII and 48 % CIII. No differences were observed between left and right ovary. Conclusion. The right ovary presented a greater size and weight, a greater number of follicular structures and a greater number of good quality CCOs.